PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS III SD NEGERI 188 PEKANBARU - Iggo Mayyudin Nugroho (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2019)
This research is in the background by the low learning outcomes of PKn-grade III students Negeri Elementary School 188 Pekanbaru, with an average class of 68.25. While the value of 40 students are only 17 students who achieve the minimum submission criteria. This research is a class action research conducted aims to improve the learning outcomes of PKn-grade III students Negeri Elementary School 188 Pekanbaru by applying a cooperative model of make a match type. The subject of this study is a grade III student of State Elementary School 188 Pekanbaru year 2018/2019. The data collection instruments on this thesis are teacher activity sheets and student activities and learning outcomes. This thesis presents the data of the learning outcomes obtained from the average learning results before the 68.25 action increased by 12.63% on average to 76.87 on the I cycle. In the II cycle it increased to 19.41% with an average of 81.5. Teacher activity on first meeting cycle I gained a percentage of 62.5% of the category enough, at the second meeting experienced an increase by a percentage of 79.16% good category. Next cycle II first meeting of teacher activity also experienced an increase with a percentage of 83.33% good category, and the second meeting experienced another increase by the percentage of 95.83% very good category. In the results of the study, students began to understand the course of PKn lessons after they had the cooperative model of the Make a match type marked with increased teacher activity and student activities and the results of learning on each cycle. The results of the research in class III of State Elementary School 188 Pekanbaru proved that the implementation of model cooperative type make a match can be a result of learning the results of PKn-grade III students Negeri Elementary School 188 Pekanbaru